Recent highlights. - Eldik, Rudi van; Hubbard, Colin D. (Advances in inorganic chemistry, 2022)
"Advances in Inorganic Chemistry, Volume 79, the latest release in an esteemed series that highlights new advances in the field of inorganic chemistry, presents new and interesting topics authored by an international field of experts."--Publisher's web page, viewed March 18, 2022.